Mechanisms, assessment, and exercise interventions for skeletal muscle dysfunction post-chemotherapy in breast cancer: from inflammation factors to clinical practice - Zhong, Pei; Li, Xizhuang; Li, Jiehua (Frontiers in Oncology, 2025)
Chemotherapy remains a central component of breast cancer treatment, significantly improving patient survival rates. However, its toxic side effects, along with cancer-related paraneoplastic syndromes, can lead to the loss of skeletal muscle mass and function, impairing physical abilities and increasing the risk of complications during treatment. Chemotherapeutic agents directly impact skeletal muscle cells by promoting protein degradation, inhibiting protein synthesis, and triggering systemic inflammation, all of which contribute to muscle atrophy. Additionally, these drugs can interfere with the proliferation and differentiation of stem cells, such as satellite cells, disrupting muscle regeneration and repair while inducing abnormal differentiation of intermuscular tissue, thereby worsening muscle wasting. These effects not only reduce the effectiveness of chemotherapy but also negatively affect patients’ quality of life and disease prognosis. Recent studies have emphasized the role of exercise as an effective non-pharmacological strategy for preventing muscle loss and preserving muscle mass in cancer patients. This review examines the clinical manifestations of muscle dysfunction following breast cancer chemotherapy, the potential mechanisms underlying these changes, and the evidence supporting exercise as a therapeutic approach for improving muscle function.